Порівняння мобільних пристроїв для монтажу з комп'ютерними - Орлеан, К. Е. (ХНУРЕ, 2025)
This work examines the question of the effectiveness of using mobile devices for video editing compared to traditional computer systems. The main ad vantages and disadvantages of both approaches are analyzed, including performance, usability, cost, and functionality. The study makes it possible to assess the prospects of mobile video editing and its potential impact on the field of con tent creation.
Keywords: монтаж пристроїв; using mobile devices